The Public Enforcement of Sanctions against Illegal Phoenix Activity: Scope, Rationale and Reform. (2016) - Welsh, Michelle; Anderson, Helen
The loss suffered by unsecured creditors of all insolvent companies is the non-payment in full of amounts rightfully owed to them. This loss is all the more unacceptable to creditors when a company has been illegally phoenixed by the transfer from the insolvent company of assets at undervalue. One way of increasing the pool of funds available for distribution to creditors is to issue proceedings seeking compensation against directors alleging that their 'phoenixing' amounted to a breach of directors' duties or insolvent trading. Such an action may be instigated by the liquidator and by ASIC. ASIC's enforcement role can be contrasted with the recovery role of the liquidator where the latter acts primarily in the furtherance of private interests, being those of the insolvent company's creditors; ASIC's mandate, on the other hand, is to act in the public interest. The purpose of this article is to examine the enforcement roles of liquidators and ASIC where suspected illegal phoenix activity has occurred. Following consideration of the difficulties faced by liquidators acting on behalf of creditors of phoenixed companies, this article considers whether it is appropriate, from a policy perspective, for the public regulator to promote private interests by exercising its enforcement powers for the benefit of creditors. The argument in favour of a publicly funded regulator seeking compensation for creditor losses is particularly compelling in the context of illegal phoenix activity, given the inability of creditors to bring enforcement proceedings themselves and the difficulties faced by liquidators when they seek redress for creditors' losses.